Characterization of low-viscosity elastic fluids in microscale - Nguyen, Nam Trung. (2010)
Microfluidics has been the focal point of research communities in recent years. Microfluidics was successfully implemented in biochemical analysis. Microfluidic applications such as lab-on-a-chip were recently introduced to the commercial market. In these applications, fluids are of biological nature with diluted polymers such as DNAs and proteins. Due to the elastic behavior of the large polymeric molecules, the liquids are non-Newtonian and viscoelastic. Despites this fact, almost all design tools for microfluidics are based on Newtonian assumption, and in particular, the elastic property of the fluids is ignored. Only recently, few works on application of viscoelastic fluids in microscale have been reported. These works reported nonlinear effects of viscoelatsic fluids in microscale. The nonlinear effects are caused by the increasing dominance of elastic force in microscale, and the decreasing significance of the inertial force. In the course of project RG-22/05 ”Characterization of Low-Viscosity Elastic Fluids in Microscale”, a number of new measurement methods for characterization of low viscosity elastic fluids were developed, implemented and characterized.